2021
DOI: 10.3390/cancers13081827
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Anti-Diabetic Drugs on Prostate Cancer

Abstract: The incidences of prostate cancer (PC) and diabetes are increasing, with a sustained trend. The occurrence of PC and type 2 diabetes mellitus (T2DM) is growing with aging. The correlation between PC occurrence and diabetes is noteworthy, as T2DM is correlated with a reduced risk of incidence of prostate cancer. Despite this reduction, diabetes mellitus increases the mortality in many cancer types, including prostate cancer. The treatment of T2DM is based on lifestyle changes and pharmacological management. Cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 136 publications
0
8
0
Order By: Relevance
“…Currently, there are several categories of antidiabetic drugs, which differ in the way they act on blood glucose level reduction, namely insulin analogues, sulphonylureas, biguanides, dipeptidyl peptidase-4 inhibitors, thiazolidiones, and α-glucosidase inhibitors, among others. Despite that, there is an ongoing effort to find out more effective and affordable antidiabetic drugs, with less side effects (American Diabetes Association 2020 ; Knura et al 2021 ). Taking advantage of the ethnopharmacological uses, plants have been selected for bioassay-guided isolation and identification of new lead antidiabetic compounds (Barzkar et al 2020 ; Gaonkar and Hullatti 2020 ; Fu et al 2021 ; Wasana et al 2021 ; Lee et al 2021 ; Ignat et al 2021 ; Abu-Odeh and Talib 2021 ).…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…Currently, there are several categories of antidiabetic drugs, which differ in the way they act on blood glucose level reduction, namely insulin analogues, sulphonylureas, biguanides, dipeptidyl peptidase-4 inhibitors, thiazolidiones, and α-glucosidase inhibitors, among others. Despite that, there is an ongoing effort to find out more effective and affordable antidiabetic drugs, with less side effects (American Diabetes Association 2020 ; Knura et al 2021 ). Taking advantage of the ethnopharmacological uses, plants have been selected for bioassay-guided isolation and identification of new lead antidiabetic compounds (Barzkar et al 2020 ; Gaonkar and Hullatti 2020 ; Fu et al 2021 ; Wasana et al 2021 ; Lee et al 2021 ; Ignat et al 2021 ; Abu-Odeh and Talib 2021 ).…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…Prostate cancer (PCa) is a tumor caused by malignant hyperplasia of prostate epithelial cells. It has a very high incidence in elderly men, with 80% of cases occurring in men over 65 years old [ 1 , 2 ]. In the early stage of PCa, most patients have no obvious symptoms due to the insidious onset and slow growth of the tumor [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes mellitus represents about 90% of diabetes cases and is one of the risk factors for the development of several cancers, such as liver, pancreas, colorectal, kidney, bladder, endometrium and breast cancer. In addition, diabetes is also associated with high levels of mortality in oncological situations, namely in PC, but several studies have shown that diabetes mellitus seems to reduce the risk of PC incidence, which appears to be related to the low plasma levels of Insulin-Like Growth Factor 1 (IGF-1) in diabetic people compared to in non-diabetic people [ 20 ].…”
Section: Pharmacotherapeutic Groups With Potential Efficacy In Pc Tre...mentioning
confidence: 99%